Larangan Menikah Bagi Pemilik Salmon Patch Perspektif Hukum Islam (Studi Kasus Desa Ledong Timur Kecamatan Aek Kuasan Kabupaten Asahan) - Abdi Nata, Wiranu; Mahmud Nasution, Muhammad (UNES Law Review, 2023)
Marriage is an act that is regulated in such a way in the provisions of Islamic law, in marriage there are pillars and conditions of marriage that must be fulfilled by every prospective bride and groom, both male and female, so that in society there are usually special prohibitions or criteria for each prospective bride and groom. . As happened in Ledong Timur Village, Aek Kuasan District, Asahan Regency, the local community believed that there was a prohibition on marrying salmon patch owners, so this attracted the attention of the author to research more deeply into why this prohibition existed and what the local ulama's views were regarding this matter. This research is qualitative research with an empirical judicial approach and the type of approach uses case studies or field studies which are usually called library research. The results of this research show that people forbid marrying salmon patch owners because they are afraid that the salmon patch owner will die in a short time. Ulama in Asahan Regency also confirmed that there was a ban in the community of East Ledong Village, however several ulama who were sources did not agree with the community's opinion regarding the ban, because for them the prohibition against marrying someone was only in Q.S An-Nisa 23-24 and Salmon patch hose is not contagious and dangerous, so both men and women can marry it.